EFEITO DE TRÊS ADUBOS FOSFATADOS SOBRE A ACIDEZ DE UM SOLO HIDROMÓRFICO - Mello, Francisco A.F. de; Arthur, Valter; Victoria, Reinaldo; Boena, Eliseu; Hernani, Luiz Carlos (REVISTA DE AGRICULTURA, 2015)
EFEITO DE TRÊS ADUBOS FOSFATADOS SOBRE A ACIDEZ DE UM SOLO HIDROMÓRFICO